2021
DOI: 10.1371/journal.pone.0256208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of captopril against radiation injuries in the Göttingen minipig model of hematopoietic-acute radiation syndrome

Abstract: Our laboratory has demonstrated that captopril, an angiotensin converting enzyme inhibitor, mitigates hematopoietic injury following total body irradiation in mice. Improved survival in mice is correlated with improved recovery of mature blood cells and bone marrow, reduction of radiation-induced inflammation, and suppression of radiation coagulopathy. Here we investigated the effects of captopril treatment against radiation injuries in the Göttingen mini pig model of Hematopoietic-Acute Radiation Syndrome (H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Local and systemic inflammation are hallmarks of radiation exposure, even at sublethal exposures [1,9,32,34,35,58]. The generation of acute inflammatory responses that we observed following total body irradiation exposure is likely due to a combination of local cellular injury/death and the loss of hematopoietic cells, triggering the upregulation of cytokines to induce the cycling/development of hematopoietic stem and progenitor cells [32,34,35,59,60]. A sustained upregulation of p21/waf1 and pro-inflammatory cytokines can occur through radiation-induced accelerated senescence, causing the activation of the senescence-associated secretory phenotype [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local and systemic inflammation are hallmarks of radiation exposure, even at sublethal exposures [1,9,32,34,35,58]. The generation of acute inflammatory responses that we observed following total body irradiation exposure is likely due to a combination of local cellular injury/death and the loss of hematopoietic cells, triggering the upregulation of cytokines to induce the cycling/development of hematopoietic stem and progenitor cells [32,34,35,59,60]. A sustained upregulation of p21/waf1 and pro-inflammatory cytokines can occur through radiation-induced accelerated senescence, causing the activation of the senescence-associated secretory phenotype [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory demonstrated that the orally available ACE inhibitor captopril can reduce the cycling of hematopoietic progenitors in vivo [32,33], and we demonstrated that captopril is an effective countermeasure in murine and Göttingen minipig models of H-ARS [32][33][34]40]. We showed that captopril-reduced mortality following TBI was associated with improved mature blood cell recovery, improved bone marrow and hematopoietic progenitor recovery, suppression of the acute inflammatory response, and the reduction of radiation coagulopathy [32][33][34][35]. Here we characterize the effects of TBI and the effects of captopril on the ileum in a Göttingen minipig model of H-ARS, including structural alterations, alterations in genes and proteins associated with iron binding and ferroptosis, and inflammatory gene expression.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our observations with ACE2 agonism after radiation injury bear many similarities to ACE inhibitor treatment in radiation injury models. For example, ACE inhibitors have been shown to increase survival during H-ARS in rodent and pig models (1,43,44). Additionally, extensive studies by our group in the rat PBI model have demonstrated ACE inhibitors mitigate lung and kidney DEARE (8,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…While anesthetized, animals were positioned in supportive slings and exposed one at a time, bilaterally, to a target total body dose of 1.79 Gy of Cobalt (60Co) radiation delivered at a dose rate of 0.485-0.502 Gy/min, as previously described. 17 After radiation procedures, each animal was transported back to the housing facility for recovery. Minipigs assigned to the sham (SH) groups were also deeply anesthetized with the same dose of Telazol/Xylazine in the housing facility but were not transported to the Cobalt facility.…”
Section: Animal Usementioning
confidence: 99%